Supply Chain Brown Sugar Agroindustry in Banyuwangi District: Analysis Study with A Dynamic System Approach - Sumadi Sumadi; Jumintono Jumintono; Fani Ardiani (International Journal of Supply Chain Management, 2020)
Abstract- The purpose of this research is to find out the basic system in the supply chain, and the dynamic system of the brown sugar supply chain in Banyuwangi Regency. This research is a combination of explanatory research and causal research and uses a system dynamics approach by considering the GAP between supply and demand for local markets. Data analysis was performed using a dynamic system simulation using the powers program with a validation test through the calculation of Mean Absolute Percentage Error (MAPE). The final results show that the basic system of brown sugar agroindustry supply chain in the Banyuwagi Regency can be identified as actors, activities, and outputs. Until 2019, the demand for meeting local brown sugar needs is greater than the supply of brown sugar in the Banyuwangi Regency. To accelerate the fulfillment of local needs for brown sugar, it is necessary to increase the productivity of the sap juice subsystem as the main raw material for the brown sugar agroindustry subsystem in the Banyuwangi Regency.